2022
DOI: 10.1002/cctc.202200493
|View full text |Cite
|
Sign up to set email alerts
|

The Synergetic Effect of Support‐oxygen Groups and Pt Particle Size in the Oxidation of α‐D‐glucose: A Proximity Effect in Adsorption

Abstract: The influence of the support‐oxygen groups and Pt particle size on the catalytic performance of Pt/AC for the aerobic oxidation of α‐D‐glucose to gluconic acid (glycolate) was studied. Surface‐oxygen groups were introduced by treating the activated carbon support with diluted HNO3 without significantly affecting the support porosity. The platinum particle size could be decreased on both the treated and untreated support by adding an additional calcination step to the synthesis. The presence of oxygen‐containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
3
7
0
Order By: Relevance
“…The formation of CO 2 (Fig. 1A) was attributed to the decomposition of carboxylic acids (100 and 400 • C), anhydrides (200 -600 • C) and lactone groups (400 -900 • C) [25][26][27]51]. CO formation (Fig.…”
Section: Effect Of Functionalization On Support Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of CO 2 (Fig. 1A) was attributed to the decomposition of carboxylic acids (100 and 400 • C), anhydrides (200 -600 • C) and lactone groups (400 -900 • C) [25][26][27]51]. CO formation (Fig.…”
Section: Effect Of Functionalization On Support Propertiesmentioning
confidence: 99%
“…As a result, it is possible to vary the point of zero charge (PZC) and consequently the acidity or basicity over a wide range. A reflux treatment of pristine carbon (in this case graphite nanoplatelets, GNP) in HNO 3 typically results in the incorporation of carboxylic, lactone and anhydride surface groups [25][26][27], increasing the acidic character of the material. An amination treatment of the oxidized carbon (GNP-O) converts the oxygen-into nitrogen-containing surface groups (GNP-N), which increase the surface basicity [22,23,28].…”
Section: Introductionmentioning
confidence: 99%
“…28 The blue triangles indicated the characteristic metallic Pt crystal structure (PDF 88-2343). 32,33 TEM and XRD prove the successful synthesis of Pt and carbide nanoparticles with a particle sizes in a similar range. CO chemisorption was used to establish the number of active sites as it is commonly used for Pt and carbide catalysts.…”
mentioning
confidence: 69%
“…28 The blue triangles indicated the characteristic metallic Pt crystal structure (PDF 88-2343). 32,33 TEM and XRD prove the successful synthesis of Pt and carbide nanoparticles with a particle sizes in a similar range.…”
mentioning
confidence: 69%
“…Previous studies have shown that electronic effects can either hinder or improve the adsorption of reactants on catalysts containing functional groups on carbon supports. According to Wang et al, , during the APR of EG over Pt catalysts supported on carbon nanotubes (CNTs), competitive adsorption occurs between the solvent and the reactant. The high polarity of hydrophilic oxygen-containing supports leads to an increase in the local concentration of water around the support, resulting in a decrease in the hydrogen turnover frequency.…”
Section: Resultsmentioning
confidence: 99%